Mechanisms of drug resistance to immune checkpoint inhibitors in non-small cell lung cancer - Zhou, Kexun; Li, Shuo; Zhao, Yi; Cheng, Ke (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) in the form of anti-CTLA-4 and anti-PD-1/PD-L1 have become the frontier of cancer treatment and successfully prolonged the survival of patients with advanced non-small cell lung cancer (NSCLC). But the efficacy varies among different patient population, and many patients succumb to disease progression after an initial response to ICIs. Current research highlights the heterogeneity of resistance mechanisms and the critical role of tumor microenvironment (TME) in ICI resistance. In this review, we discussed the mechanisms of ICI resistance in NSCLC, and proposed strategies to overcome resistance.